THE EFFECT OF EDUCATION INFORMATION NETWORK (EBA) AND EXPERIMENTAL-BASED INSTRUCTION ACTIVITIES ON 7TH GRADE STUDENTS’ SCIENCE ATTITUDE AND THEIR VIEWS ABOUT THESE ACTIVITIES IN THE ELECTRICAL CIRCUITS UNIT - Sarikaya, Dilek; Aydin, Abdullah (International Online Journal of Education and Teaching, 2022)
The aim of this study is to investigate the effectiveness of the Education Information Network (EBA) and experimental supported activities on students’ science attitude and 7th grade students’ views about these activities in the teaching of the electrical circuits unit. The research was carried out with 73 students studying at a state secondary school in the Daday district of Kastamonu Province, Turkey in the second semester of the 2018-2019 academic year. Two experimental groups and one control group were randomly selected from school. While the courses of the experimental-1 group were taught with the EBA supported activities, the experimental-2 group were taught with the EBA and experimental activities, the courses of the control group were taught in compliance with the 2018 Science Curriculum. In research, quantitative data were collected with the Science Course Attitude Scale (SCAS) and qualitative data were collected with the Semi-Structured Interview Form (SSIF). As a result of this study, while there was no significant difference between the experimental-1 group and the control group, it was observed that there is a significant difference between experimental-2 group and control group, and experimental-2 group and experimental-1 group. In other words, EBA and experimental-supported teaching improved positively students’ attitudes towards the science course. The data obtained from SSIF applied only to six students from the experimental-2 group support this result. Based on the results of the study, science teachers are recommended to do experimental with EBA in their courses.